Platelet Immunophenotyping by High‐Dimensional Mass Cytometry. Issue 5 (5th May 2021) - Spurgeon, Benjamin E. J.; Michelson, Alan D.; Frelinger, Andrew L.
Abstract: Platelets are small blood cells that contribute to hemostasis, immunity, and inflammation. Characterization of platelet surface markers allows for differentiation of activated platelets from resting platelets, diagnosis of platelet disorders, and investigation of platelet biology and pathology. In this article, we describe the use of mass cytometry or "CyTOF" (mass spectroscopy detection of metal‐tagged antibodies on individual cells) to measure a large number of markers on each platelet and to identify platelet subsets based on the shared expression of multiple markers. This powerful new approach provides a vastly more detailed picture of platelet immunophenotypes than conventional flow cytometry and enables investigation of the roles of platelet subsets in health and disease. © 2021 Wiley Periodicals LLC. Basic Protocol : Platelet immunophenotyping by high‐dimensional mass cytometry Support Protocol : Data preprocessing